The new trend for antiseizure medication selection in juvenile myoclonic epilepsy: A retrospective multi-center study from Turkey between 2010 and 2020 - Aydın, Kürşad; Kılıç, Betül; Serdaroğlu, Esra; Gönüllü Polat, Burçin; İnce, T.; Esenülkü, Gülnur; Topçu, Yasemin; Serdaroğlu, Ayşe; Haspolat, Şenay; Tekgül, Hasan; Okuyaz, Çetin; Cansu, Ali (Wiley, 2022)
[Abstract Not Available]
Keywords: Juvenile Myoclonic Epileps; Antiseizure Medication; Turkey; 2010 and 2020